Social Construction Of Jaran Jenggo “Aswo Kaloko Joyo” In Solokuro Village - yudistira, alvina; suryandoko, welly (Solah, 2025)
Jaran Jenggo is a traditional art form that originated in Lamongan Regency, specifically in the Solokuro region. During circumcision ceremonies, this art form takes the form of a procession in which the bride, who has undergone circumcision, rides a horse controlled by a handler and accompanied by various attractions. This tradition began in 1907 and continues to this day. This study aims to describe how the Jaran Jenggo community shapes and maintains its cultural identity through language, symbols, and social interactions. The study employs a descriptive qualitative method, using data collection techniques such as direct observation, in-depth interviews, and documentation. According to Berger and Luckman's social construction theory, there are three stages: externalization, objectification, and internalization. This study aims to describe the social construction of Jaran Jenggo art. According to the research findings, the externalization of Jaran Jenggo art originated from the tradition of using horses during the missionary activities of Sunan Drajat and Sunan Sendang Duwur. This tradition was then inherited and developed into a unique performance art in Lamongan. Jaran Jenggo's objectification is reflected in the symbolic, spiritual, and local cultural identity values inherent in its movements, costumes, and language. Internalization occurs through primary and secondary socialization, which involves individuals from an early age and integrates them into the wider community. This ensures that the art form is preserved and accepted as an integral part of the Lamongan community's social life.